Pengaruh Penyuluhan tentang Baby Spa pada Bayi Usia 3-6 Bulan terhadap Pengetahuan Ibu - Samudra, Selfi Berliana; Rukmaini, Rukmaini; Novelia, Shinta (Jurnal Akademika Baiturrahim Jambi, 2024)
Currently, there are many baby spa facilities appearing, but there are still many parents who don't know about baby spas and their benefits. Parents pay more attention to good nutrition for their babies, but baby spa has many benefits for babies, especially to improve their blood circulation, muscles, nerves and movement development. The aim of the research was to determine the effect of education about baby spas on mothers' knowledge about the importance of baby spas at Pinguin Mom and Baby Care Cirebon in 2022. The research used an experimental design with a one group pre test post test design. The population used in this study were all mothers with babies aged 3-12 months who visited Pinguin Mom and Baby Care Cirebon in the period March to June 2022, namely 34 people. The results of the Wilcoxon Signed Rank Test statistical test show a p value of 0.001 ≤ 0.05, meaning that there is a difference in mothers' knowledge before and after being given counseling about the importance of baby spas at Pinguin Mom and Baby Care Cirebon in 2022. There is an influence of counseling about baby spas on knowledge mothers about baby spa at Pinguin Mom and Baby Care Cirebon in 2022. Suggestions are expected to further increase knowledge and skills about the importance of baby spa by attending counseling, health education or consulting with health workers, so that they can carry out baby spa independently and correctly to improve their status. the health of the baby and reducing maternal and infant mortality rates